Hubungan Pengetahuan tentang Kanker Payudara dengan Perilaku Pemeriksaan Payudara Sendiri (SADARI) pada Remaja Putri di MA Muhammadiyah 1 Kota Malang - Salsabila Ifada; Herawati Mansur; Desy Dwi Cahyani (Pusat Riset dan Inovasi Nasional, 2025)
In Malang City, breast cancer is recorded as the second most common cancer in East Java. Based on data from 2021–2022, the number of breast cancer cases in Malang increased to 29 cases. This indicates that breast cancer remains a serious public health problem requiring special attention, particularly in terms of prevention and early detection. One of the simplest early detection efforts that can be carried out independently is breast self-examination (BSE). However, the practice of BSE among adolescent girls is strongly influenced by their level of knowledge regarding breast cancer. The purpose of this study was to determine the relationship between knowledge about breast cancer and breast self-examination behavior among adolescent girls at MA Muhammadiyah 1 Malang. This research employed an analytical correlation method with a cross-sectional approach. The study population consisted of 85 students, with a sample of 46 students selected through proportional random sampling. The research instruments included a breast cancer knowledge questionnaire and a BSE behavior questionnaire that had been tested for validity. The results showed that the level of knowledge among adolescent girls at MA Muhammadiyah 1 Malang was mostly in the moderate category. Similarly, their BSE behavior was also predominantly in the moderate category. Data analysis using the Chi-Square statistical test revealed a significant relationship between knowledge about breast cancer and breast self-examination behavior, as indicated by a p-value = 0.022 (<0.05), which means the research hypothesis was accepted. In conclusion, the findings suggest that better knowledge of breast cancer is associated with better BSE behavior among adolescent girls. Therefore, continuous efforts in the form of communication, information, and education (CIE) on early detection of breast cancer are necessary. Improved knowledge is expected to raise awareness and encourage adolescent girls to routinely perform BSE as a preventive measure against breast cancer